Gaming technologies application in supplementary education of children - Homik E. N., Soshenko L. N., Kuzmina Y. A. (Pedagogical excellence and pedagogical technologies, 2016)
The actuality of using gaming technology in the system of modern additional education of children is being discussed in the article. In conclusion, the authors concluded that it is important to use gaming technology, contributing to the development of cognitive activity, the revitalization of the pupils, to support interest in the studied material and remove fatigue from children.
Keywords: игровые технологии; дополнительное образование детей; педагогическая игра; дидактическая игра; технология обучения; didactic game; game technologies; pedagogic game; training technology; supplementary education of children